?TRACE ELEMENT STUDIES IN UROLITHIASIS: PRELIMINARY INVESTIGATION ON CALCIUM OXALATE AND MIXED CALCIUM OXALATE-HYDROXYAPATITE URINARY CALCULI (Biological Sciences - PJSIR, 1995)
In this preliminary investigation, the levels of the trace elements copper, zinc, magnesium, lead, iron, aluminium, nickel, chromium, sodium and potassium were estimated in seven calcium oxalate (CaOx) and six mixed calcium oxalate-hydroxyapatite (CaOx/APA) urinary calculi. The results were compared with those from South Africa, Turkey and Austria. Our mean results fortheCaOx and CaOx/APAcalculi were respectively, copper4.3, 7.15 ng/mg; zinc 141.8, 191.1; magnesium 18520,7203; lead 21.7, 15.5; iron 24.7, 78.35; aluminium 14.3,42.7; nickel 0.39, 0.85; chromium 1.52, 1.88; sodium 4057, 3260; potassium 200, 150ng/mg, Only for aluminium was the difference significant: 0.05>p>0.02.